The Emergence and Construction of the Memory of the Shoah in Greece (1945–2015): From Oblivion to Memory - Varon-Vassard, Odette (Historein, 2019)
The genocide of the Greek Jews was almost total, with the extermination rate of more than 80 percent much higher than in most Western European countries. Nonetheless, the decades that followed the end of the war, the liberation of the camps and the difficult return of the survivors were ones of silence. Greece was no exception to the oblivion that shrouded the event for decades internationally. On the contrary, compared to other Western countries, there was a longer delay in recognising this memory at the level of both the state and of society. If it was established internationally in the 1980s, this memory (and the associated historical studies and publication of testimonies) in Greece began in the early 1990s. Since 2004, the interest of the state began to manifest itself in practice. Even so, the question remains whether this memory has been recorded in the collective memory of Greek society. This article attempts to outline the long and painful course from oblivion and silence to the emergence and reconstruction of the cultural memory of the Shoah in Greece, noting the most significant events that it comprises.